(3JHUQI GdeHJOi hJPcQg GdefJgis - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s
(3ChdgG (B:s
(3GdeLdS GdKGdK ef GdWHbI GdQGHYI UOQg ai PcQ GdUdhGJ hYLRg (B: (3Ef GdPjf SHbJ dge efG GdMSfi GdMeO ddg GdPi ChVM SHjd gOGjJg dGQHGH hdGjJg s
(3BNQgG (B:s
(3aEf cfJe HGdZadI bO fSjJe hLfjJe hMhTjJe aGYedhG eGTjJe BNQ GdLRA GdKGdK ef cJGH JHUQI GdeHJOF hJPcQg GdefJgi hjJdhg GdLRA GdQGHY GdeLdS GdNGeS hGdYTQhf ai GdeMHI ai Gddg JYGdi s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(307 (3b(B) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs